On the presence of Phoracantha recurva Newman and Phoracantha semipunctata F. ( Coleoptera Cerambycidae) in Calabria (Bollettino di zoologia agraria e bachicoltura, 2024)
The authors report on the contemporary presence of the Eucaliptus longhomed borers Phoracantha recurva Newman and Phoracantha semipunctata F. in the entomological collection of the Department of GESAF of the Mediterranea University of Reggio Calabria. Subsequently P. recurva was observed to occur in Eucaliptus woods in Calabria and it can be easily differentiated from P. semipunctata through the stains pattern on elytrae, the pilosity on antennae and the dorsal face spines on posterior femurs.
Keywords: Eucaliptus; Calabria; Italy; Avetianella longoi; Eucaliptus longhorned borers